Impact of Corporate Social Responsibility on Brand Value and the Mediating Role of Reputation, Image and Brand Loyalty: A Case study of three private higher education institutions in Peru - Yessica ERAZO-ORDOÑEZ; Elizabeth Emperatriz GARCÍA-SALIRROSAS and Roberto MACHA-HUAMÁN (Communications of International Proceedings, 2024)
In recent years, CSR actions have taken center stage in various organizations, including the higher education sector; the growing demand for sustainable practices on the part of students has led them to include them in their management, knowing that it has an impact on reputation and brand image.   The objective of this study is to analyze to what extent CSR influences brand value, taking as mediating variables image, reputation and brand loyalty in private higher education institutions in Peru. The study has a quantitative approach, with a non-experimental design, cross-sectional and explanatory level through a structural equation model. The study sample consisted of 381 students from 3 private universities in the capital of Peru. The results of the theoretical model were accepted because the values of RMSEA= 0.056 and SRMR=0.024 are very close to zero, the CFI =0.974, Chi-square (X^2)= 110 and (df)=50. It was also found that CSR influences brand image (β=0.36), influences brand reputation(β=0.84) and influences brand loyalty (β=0.28).Likewise, reputation, a mediating variable influences brand image(β=0.49), brand loyalty (β=0.58) and brand equity(β=0.30). In addition, brand image influences brand equity (β=0.27) and brand loyalty influences brand equity (β=0.36). It is concluded that well-targeted CSR actions influence brand equity through the variables brand image, brand reputation and brand loyalty.
Keywords: Corporate Social Responsibility; Brand Value; Reputation; Image; Brand Loyalty; universities; Peru.